One-step fabrication of core–shell structured alginate–PLGA/PLLA microparticles as a novel drug delivery system for water soluble drugs - Lim, Ming Pin Alan (2016)
Current focus on particulate drug delivery entails the need for increased drug loading and sustained release of water soluble drugs. Commonly studied biodegradable polyesters, such as poly(lactide-co-glycolide) (PLGA) and poly(L-lactide) (PLLA), are lacking in terms of loading efficiency of these drugs and a stable encapsulation environment for proteins. While hydrogels could enable higher loading of hydrophilic drugs, they are limited in terms of controlled and sustained release. With this in mind, the aim was to develop microparticles with a hydrophilic drug-loaded hydrogel core encapsulated within a biodegradable polyester shell that can improve hydrophilic drug loading, while providing controlled and sustained release. Herein, we report a single step method of fabricating microparticles via a concurrent ionotropic gelation and solvent extraction. Microparticles fabricated possess a core–shell structure of alginate, encapsulated in a shell constructed of either PLGA or PLLA. The cross-sectional morphology of particles was evaluated via scanning electron microscopy, calcium alginate core dissolution, FT-IR microscopy and Raman mapping. The incorporation of alginate within PLGA or PLLA was shown to increase encapsulation efficiency of a model hydrophilic drug metoclopramide HCl (MCA). The findings showed that the shell served as a membrane in controlling the release of drugs. Such gel-core hydrophobic-shell microparticles thus allow for improved loading and release of water soluble drugs.